مبدأ وجود أساس فعال لحوكمة الشركات و أثره في تعزيز جودة الإفصاح المحاسبي دراسة اتجاه بعض آراء الأكاديميين والمهنيين - سفير, محمد; صحراوي, ياسين (Université de M'sila, 2019)
الملخص: تهدف هذه الدراسة إلى معرفة تأثير حوكمة الشركات من خلال مبدأ وجود أساس محكم وفعال لحوكمة الشركات، على جودة الإفصاح المحاسبي. وهذا بدراسة أراء مجموعة من الأكاديميين والمهنيين. حيث تم توزيع استبيان وتحليله باستخدام البرنامج الإحصائي (spss). توصلت نتائج هذه الدراسة إلى وجود أثر قوي وفعال وايجابي لتطبيق مبدأ وجود أساس فعال ومحكم لحوكمة الشركات في إيجاد إفصاح ذو جودة. كما توصلت الدراسة إلى أنه لا يوجد أي تأثير حول تطبيق هذه المبدأ على جودة الإفصاح المحاسبي. وتوصي الدراسة بضرورة تطبيق مبادئ حوكمة الشركات من خلال توفير الإطار التشريعي والقانوني لها، إضافة إلى تدريب وتأهيل الأطراف المعنية بتطبيقها. الكلمات المفتاحية : حوكمة الشركات، إفصاح محاسبي، جودة المعلومة المحاسبية، تقارير مالية. Abstract : This study aims at identifying the impact of corporate governance on the basis of the principle of a strong and effective basis for corporate governance on the quality of accounting disclosure. Where we studied the views of a group of academics and professionals. For this purpose, a questionnaire was prepared, distributed and analyzed using the statistical program (spss). The results of this study have found a strong, effective and positive impact on the application of the principle of an effective and firm basis for corporate governance in finding quality disclosure. The study also found that there is no impact on the application of this principle on the quality of accounting disclosure. The study recommends the application of the principles of corporate governance by providing the legislative and legal framework, in addition to training and rehabilitation of the parties concerned to implement them. Keywords : Corporate Governance, Accounting Disclosure, Quality Accounting Information, Financial Reports.
Keywords: حوكمة الشركات، إفصاح محاسبي، جودة المعلومة المحاسبية، تقارير مالية. ; Corporate Governance, Accounting Disclosure, Quality Accounting Information, Financial Reports